Tourette's syndrome and deep brain stimulation. Issue 7 (16th June 2005) - Houeto, J L; Karachi, C; Mallet, L; Pillon, B; Yelnik, J; Mesnage, V; Welter, M L; Navarro, S; Pelissolo, A; Damier, P; Pidoux, B; Dormont, D; et al.
Abstract : In this prospective double blind randomised "N of 1" study, a patient with a severe form of Tourette's syndrome was treated with bilateral high frequency stimulation of the centromedian-parafascicular complex (Ce-Pf) of the thalamus, the internal part of the globus pallidus (GPi), or both. Stimulation of either target improved tic severity by 70%, markedly ameliorated coprolalia, and eliminated self injuries. Severe forms of Tourette's syndrome may benefit from stimulation of neuronal circuits within the basal ganglia, thus confirming the role of the dysfunction of limbic striato-pallido-thalamo-cortical systems in this disorder.